2005
DOI: 10.1074/jbc.c500181200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lysine 56 of Histone H3 as an Acetylation Site in Saccharomyces cerevisiae

Abstract: Post-translational histone modifications abound and regulate multiple nuclear processes. Most modifications are targeted to the amino-terminal domains of histones. Here we report the identification and characterization of acetylation of lysine 56 within the core domain of histone H3. In the crystal structure of the nucleosome, lysine 56 contacts DNA. Phenotypic analysis suggests that lysine 56 is critical for histone function and that it modulates formamide resistance, ultraviolet radiation sensitivity, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
116
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 22 publications
8
116
1
1
Order By: Relevance
“…4 Using cell division cycle (cdc) mutants to arrest yeast cells at different stages of the cell cycle, high levels of K56 acetylation were also detected outside of S-phase. 5 All the studies of K56 acetylation thus far were performed with five distinct affinity-purified polyclonal antibodies raised against synthetic peptides. [4][5][6][7][8] The specificity of all these antibodies for K56 acetylation was rigorously demonstrated by the absence of signal in yeast strains where histone H3 K56 was mutated into a nonacetylatable residue.…”
Section: H3 K56 Acetylation: Where and When?mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Using cell division cycle (cdc) mutants to arrest yeast cells at different stages of the cell cycle, high levels of K56 acetylation were also detected outside of S-phase. 5 All the studies of K56 acetylation thus far were performed with five distinct affinity-purified polyclonal antibodies raised against synthetic peptides. [4][5][6][7][8] The specificity of all these antibodies for K56 acetylation was rigorously demonstrated by the absence of signal in yeast strains where histone H3 K56 was mutated into a nonacetylatable residue.…”
Section: H3 K56 Acetylation: Where and When?mentioning
confidence: 99%
“…1,2 Six independent research groups recently reported the discovery of lysine 56 as a novel site of histone H3 acetylation in the budding yeast Saccharomyces cerevisiae. [3][4][5][6][7][8] K56 acetylation has also been observed in the fission yeast Schizosaccharomyces pombe, 6 which is evolutionarily very distant from S. cerevisiae. 9 Based on mass spectrometry, K56 acetylation occurs in Plasmodium falciparum (A. Salcedo and H. Stunnenberg, in preparation) and the modification has also been reported in Drosophila.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations